Inter Condylar Notch Width Index among Anterior Cruciate Ligament Injury Patients - Maharjan, Lokeshwor; Maharjan, Rajram; Chaurasia, Roshan Bhagat; Regmi, Shubhekshya; Maharjan, Suvekshya (Nepal Journal of Health Sciences, 2024)
Introduction: The anterior cruciate ligament (ACL) is one of the major stabilizers of the knee joint and is commonly injured. It has been shown that narrow notch houses thinner ACL, and has high chance of ACL- notch impingement during knee movement. Several other studies show that smaller notch width index (NWI) is associated with the risk of ACL rupture in the skeletally immature population. Objective: This study was done to evaluate the association of intercondylar notch index with ACL injury. Methods: A cross sectional comparative study was conducted in Department of Orthopedics, National Trauma Center, Nepal in 42 patients above 18 years of age with clinical suspicion of ACL injury. Based on the magnetic resonance imaging, patients with knee injuries were classified into ACL injury and Non- ACL injury group which was considered as controls. Case and controls were then compared based on notch width index. Results: Age of the patients ranged from 19 to 54 years with the mean age of 34.02±7.83 years. The mean NWI was 0.241±0.013 which was less than the NWI of 0.259±0.014 in the control and it was statistically significant with the p-value of <0.001. Conclusion: Low notch width index (NWI) was found in ACL injury group compared to non-ACL injury group and it was statistically significant.